Optimal Design of Solar Roof Top Photovoltaic Plant Under Various Operating Conditions - Amulya H.G. (International Journal of Photochemistry and Photochemical Research, 2024)
As conventional energy sources are quickly exhausted, the need to switch to sustainable alternatives has never been more urgent. The transition from conventional energy resources to renewable sources, particularly solar energy, has emerged as a pivotal step towards sustainable development This paper explores the advantages of solar power plants, with a focus on rooftop solar installations. Installing solar panels on a roof is revolutionizing the industry. The design phase of a solar power plant is a critical stage that lays the foundation for its long-term performance, efficiency, and economic viability. This project presents detailed designing process of a solar power plant, encompassing technical consideration, various layouts and key elements essential for successful implementation. However, rooftop solar plant faces several challenges, ranging from technical constraints to financial barriers. This paper sets out the technique and significance of planning and simulating a 116KWP demo site with solar roof top plant. Firstly, it begins with a comprehensive site assessment that is portion of the design process which includes several critical steps. To ensure maximum solar irradiance and energy output, terminologies such as roof orientation, tilt angle, shading and available space should be attentively evaluated. Moreover, local regulations, building codes, and structural integrity are important in ensuring that designs comply with standards and safety regulations. Simulation is instrumental in assessing the performance of the proposed design under different circumstances. Affordable software tools permit accurate modelling of parameters like solar irradiance, panel efficiency, system losses and financial projections. By simulating various configurations and parameters, one can find best options in terms of design that maximize electricity produced.
Keywords: Design; Roof top; Simulation; Solar plant; efficiency; solar irradiance